SEPARATION AXIOMS BETWEEN T-0 AND T-1 ON LATTICES AND LATTICE MODULES - (:unkn) unknown (FORUM EDITRICE UNIV UDINESE, 2016)
In this study, we characterize the lattices and lattice modules whose prime spectrum satisfy some of the separation axioms between T-0 and T-1. This characterizations are the notion of pm-lattice, m-lattice, epsilon-lattice, e.t.c. Similarly, this characterizations are the notion of PM-lattice module, mu-lattice module, epsilon-lattice module, etc.
Keywords: separation axioms; prime element; prime spectrum; ZARISKI TOPOLOGY; PRIME SPECTRUM